A Literary Review Of Pathya And Apathya W.S.R To Aamvata - Sharma, Punita; Yadav, Chhaju Ram; Jolly, Neha; Chouhan, Dinesh C (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is not merely a medical science. It is a complete life science. To maintain the health of a healthy person. Ayurveda gives importance to diet and regimen. The concept of Pathya (wholesome) and Apathaya (unwholesome) is one such concept. Ayurveda deals with the Pathya, Apathya or Pathya Vyavastha(planning of diet dietetics) in a very scientific and holistic way of Dietetics .Apart from being a part of regime of healthy living, Acharya had also extended the concept of Pathya (wholesome)and Apathaya (unwholesome) as a part of the treatment of the diseases. Pathya and Apathya has a major role in the management of disease. In some stages of disease following Pathya and avoiding Apathya is enough to cure the disease. Aamvata is one of the such a disease. Aamvata is a disease in which vitiation of VataDosha and accumulation of Ama take place in joints, which is similar to rheumatoid arthritis (RA) in modern. Ama is a maldigested product, which is not homogeneous for the body. Whenever that Ama gets localized in the body tissue or joints, it can lead to production of pain, stiffness, swelling, tenderness, etc. This is anAgni related disease and in these types of disease,Pathya and Apathya is having great importance, considered as half treatment. Many Acharya mentioned the Pathya and Apathya of Aamvata.It is a Vata related disease hence the Aahar and Vihar which decrease Vata in the body is Pathya and which increase Vata is Apathya for Aamvata.So, in this paper we are going to discuss the fundamental principles of Pathya Vyavastha(Dietetics) with appropriate references, recommended, diet based on the text w.s.r to Aamavata